Transcranial focused ultrasound stimulation with high spatial resolution - Seongyeon Kim; Yehhyun Jo; Geon Kook; Cristina Pasquinelli; Hyunggug Kim; Kipom Kim; Hyang-Sook Hoe; Youngshik Choe; Hyewhon Rhim; Axel Thielscher; Jeongyeon Kim; Hyunjoo Jenny Lee (Brain Stimulation, 2021)
Background: Low-intensity transcranial focused ultrasound stimulation is a promising candidate for noninvasive brain stimulation and accurate targeting of brain circuits because of its focusing capability and long penetration depth. However, achieving a sufficiently high spatial resolution to target small animal sub-regions is still challenging, especially in the axial direction. Objective: To achieve high axial resolution, we designed a dual-crossed transducer system that achieved high spatial resolution in the axial direction without complex microfabrication, beamforming circuitry, and signal processing. Methods: High axial resolution was achieved by crossing two ultrasound beams of commercially available piezoelectric curved transducers at the focal length of each transducer. After implementation of the fixture for the dual-crossed transducer system, three sets of in vivo animal experiments were conducted to demonstrate high target specificity of ultrasound neuromodulation using the dual-crossed transducer system (n = 38). Results: The full-width at half maximum (FWHM) focal volume of our dual-crossed transducer system was under 0.52 μm3. We report a focal diameter in both lateral and axial directions of 1 mm. To demonstrate successful in vivo brain stimulation of wild-type mice, we observed the movement of the forepaws. In addition, we targeted the habenula and verified the high spatial specificity of our dual-crossed transducer system. Conclusions: Our results demonstrate the ability of the dual-crossed transducer system to target highly specific regions of mice brains using ultrasound stimulation. The proposed system is a valuable tool to study the complex neurological circuitry of the brain noninvasively.